Faktor Risiko yang Berhubungan dengan Kejadian Obesitas pada Remaja (Studi Kasus di SMA Negeri 15 Semarang) - Marshella Agita Kemala Sari; Yanesti Nuravianda Lestari (Media Gizi Kesmas, 2024)
Background: One of the nutritional problems in adolescents is obesity. Risk factors for obesity are multifactoral.Imbalanced consumption of nutrients, high salt consumption, insufficient fiber intake, increased frequency ofconsumption of junk food, low physical activity, genetic factors, psychological factors, socio-economic status, dietprograms, age and gender are factors that contribute to adolescent obesity.Objective: Analyze to determine the risk factors associated with the incidence of adolescent obesity.Method: Case control study with a total of 80 subjects, cases are obese adolescents and controls are non-obeseadolescents. The sampling technique used was purposive sampling. The independent variables are the level ofadequacy of macronutrient intake, fiber intake, sodium intake, frequency of junk food consumption, physicalactivity level, sleep quality, and stress level. The attachment variable is the incidence of obesity in adolescents.Data analysis used the chi-square test and multiple logistic regression.Results: Risk factors that were significantly related (p<0.05) to risk factors for obesity in adolescents were energyintake (p = 0.000); protein intake (p = 0.018); fat intake (p = 0.000); carbohydrate intake (p = 0.001); fiber intake(p = 0.007); sodium intake (p = 0.000); frequency of junk food consumption (p = 0.023); and physical activity (p= 0.000). The results of the multiple logistic regression test showed that carbohydrate intake was the mostdominant risk factor for obesity (Exp(B) = 18,743; 95%CI = 2,778-126,457; p = 0.003).Conclusion: Adolescents with excessive intake of macronutrients and sodium, insufficient fiber intake, frequentconsumption of junk food, and low levels of physical activity are at greater risk of obesity. Keywords: Adolescent, Obesity, Risk factors